Exploratory Study of the Integration of Socio-Emotional Learning in English Language Learning in Primary School: Opportunities and Challenges - Ita Sarmita Samad; Mustakim Mustakim; Fitriyani Fitriyani; Ismail Ismail (Universitas Muhammadiyah Enrekang, 2025)
This study aims to explore the forms and strategies of integrating Social Emotional Learning (SEL) in English learning in elementary schools, as well as identify opportunities and challenges that arise in its implementation. This study uses a qualitative approach with an exploratory study design. The research subjects consisted of six female English teachers who taught elementary school students in English course institutions. Data was collected through in-depth interviews and classroom observations, then analyzed using a thematic analysis approach. The results show that teachers have implicitly integrated SEL principles in learning practice through various strategies, such as creating a positive and inclusive learning atmosphere, using collaborative activities such as games and storytelling, and providing positive reinforcement to foster students' empathy and confidence. SEL integration has been proven to open opportunities for strengthening social relationships between students, increasing learning motivation, and developing a more balanced character between cognitive and affective aspects. However, this study also found a number of challenges, including time constraints, the dominant focus on learning aspects, and the lack of teacher training in the systematic implementation of SEL. The results of this study confirm the importance of institutional support and the development of contextual SEL-based learning models in English learning at the elementary school level.